Premarital education (PME) program through online media to increased healthy lifestyle patterns on stunting prevention - Yuniarti, Falasifah Ani; Che Hasan, Muhammad Kamil; Huriah, Titih; Dhifananda, Aura Zahra Oceani; Japar, Salimah (AIP Publishing, 2024)
Indonesia is currently one of the countries with a higher prevalence of stunting than other Southeast Asian countries in 2019. Yogyakarta Special Region (DIY) is one of Indonesia’s provinces that has stunting problems. This study aims to determine the influence of pre-marital education (PME) programs through online media on improving healthy living behavior patterns to prevent stunting. This research uses quantitative methods with a quasi-experimental research design with a pretest-posttest design and a control group design. Respondents to the study totaled 76 premarital couples using purposive sampling techniques, divided into intervention groups and control groups. The data analysis in this study used the Wilcoxon signed rank test and the Mann-Whitney test. Healthy lifestyle behavior patterns are measured using the Health-Promoting Lifestyle Profile II (HPLP-II) questionnaire. This study showed that there was an increase in healthy lifestyles regarding stunting prevention in premarital couples after being given the intervention of the Premarital Education (PME) program through online media in the form of posters and videos. The results showed that most of the respondents in the intervention group had a healthy lifestyle pattern (97.4%), and a healthy lifestyle was not good (2.6%) after being given the intervention. In contrast, the control group had a healthy lifestyle (37.9%), and a healthy lifestyle was not good (42.1%) after being given the intervention. The results of the Mann-Whitney Test showed that with a p-value of 0.000 or p <0.05, it can be concluded that there are differences in the healthy behavior patterns of premarital couples in the intervention group and control group after being given PME. Health education through online media about stunting before marriage will influence new couples to implement healthy lifestyles to prevent stunting in their future children.